HUBUNGAN PERAN ORANG TUA, TEMAN SEBAYA, MEDIA INFORMASI DAN PERSEPSI REMAJA DENGAN PERILAKU SEKSUAL REMAJA - Oktavianis Oktavianis; Nurhayati Nurhayati; Novi Rahmadani (Maternal Child Health Care, 2021)
Sexual behavior is any behavior that is driven by sexual desire, ranging from feelings of interest to behavior of dating, making out and sex. The purpose of this study was to determine The Correlation between the Role of Parents, Peers, Information Media and Adolescent Perceptions Toward Adolescent Sexual Behavior in Junior High School Students in Kubung District, Solok Regency in 2021. The type of this study was descriptive analytic with a cross sectional approach. It was carried out on August 2021. The population was students in the second and the third grade of junior high school in Kubung, Solok Regency. They were 929 people. 90 students had been chosen by proportional stratified random sampling technique. The data were collected by questionnaire and it was analyzed by univariate and bivariate data analysis by using Chi-square test. The results obtained that adolescents whose parental roles were negative about sexual behavior were 52.2%, adolescents who had positive peers were 61.1%, adolescents who were not exposed to information media were 83.3%, adolescents who had positive perceptions about sexual behavior were as many as 51.1%, while sexual behavior balanced between adolescents who behaved sexually risky and not at risk is 50%. Last, it can be concluded that there was a relationship between peers and information media with adolescent sexual behavior Junior High School Students in Kubung District, Solok Regency in 2021. It is hoped that schools can be more optimal in providing guidance and counseling for the prevention of adolescent sexual behavior.